Implementation of the Islamic Mentoring Learning Model in Developing Students’ Religious Character at SD IT Amanah Sungai Penuh City - Anggrein, Are Nur; Candra, Hadi (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
This study aims to analyze the planning, implementation, and evaluation of the Islamic Mentoring learning model in developing the religious character of students at SD IT Amanah Sungai Penuh City. A qualitative descriptive method was employed, involving principals, Islamic mentoring teachers, and students from grades 4–6. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that planning is carried out by preparing lesson plans, grouping students by gender, and selecting learning materials from Arrasyad books (Volumes 1–6), covering Qur'an, Aqidah, Hadith, Sirah, Fiqh, Akhlak, and skills. Implementation is conducted weekly in small groups of 10–15 students, starting with greetings, Qur’an recitation, and thematic discussions on Islamic values, supported by teacher role modeling. Evaluation is performed through daily attitude monitoring (mutaba’ah yaumiyah), oral questioning, and observation of behavioral changes. The model effectively improved students’ religious character in terms of worship discipline, polite speech, mutual respect, and environmental awareness. This research concludes that Islamic mentoring, when well-planned and consistently implemented, plays a significant role in shaping students’ religious character in primary Islamic integrated schools.